WOMEN EMPOWERMENT IN ACEH : COMMUNITY SELF RELIANCE GROUP ON WOMEN - Srimulyani, Eka; Inayatillah, Inayatillah (Universitas Islam Negeri Ar-Raniry, 2015)
This research is examining the model of Kelompok Swadaya Masyarakat (Community Self Reliance Groups) in empowering and increasing the socio-economic situation of women, based on some case study in Acehnese community. Microfinance program has been frequently associated with women as usually the program targets women as their beneficiaries, particularly the microfinance group model. There have been some optimistic and pessimistic perspectives on how microfinance could improve the economic situation of women. Some argued that microfinance would increase the income generating of women, while others doubted as it is very little and micro, this would not help much in improving the economic situation of women. This research is not focusing on examining the economic impact of the program, but instead the non-economic impact of the program in empowering women’s personal and social capital by looking at group based microfinance program. The research tried to answer the questions of how the microfinance program could affect the non-economic situation of women, and what kind of personal and social capabilities affected by the program. Through several interviews, questionnaires and FGDs (focused group discussion) in some selected regions through purposive sampling, the study showed that this model has relatively affected the women’s personal and social capabilities. Most of the group members mentioned the increase of their self confidence and strong social networking that they benefited after joining the program. In some cases, the program has affected the ‘political’ skill in conveying their voice through their leadership experiences in the group. Moreover, putting the context of post conflict and tsunami disaster of Aceh, the program has been a ‘place’ for them to get relief from the psychological/traumatic and social impacts of the disasters, and also contribute to conflict resolution in a sophisticated way. Keywords: